In vitro antisickling activities of two indigenous plant recipes in Ibadan, Nigeria - I.T. Gbadamosi; S.B. Adeyemi; A.A. Adeyemi; J.O. Moody (International Journal of Phytomedicine, 2012)
In view of the prevalence sickle cell disease in Nigeria, the use of herbs for treatment of diseases due to high poverty level and inadequate distribution of health care centres in the country, two indigenous recipes consisting of six ethnobotanicals used in the management of sickle cell anaemia in Nigeria were screened for antisickling activity. Recipe 1 constituents were Detarium microcarpum (Guill. and Perr.), Harungana madagascariensis (Lam. ex Poir), Sorghum bicolor (Linn.), Tetracera potatoria (Afzel. ex G. Don) and Theobroma cacao (Linn.). Recipe 2 was a monorecipe of Phyllanthus amarus (Schum and Thonn). Clinical blood samples of confirmed non-crisis sickle cell patients (male and female) were collected from the Department of Haematology, University College Hospital (UCH), Ibadan, Nigeria. Extracts of the recipes were prepared in 80% ethanol using cold extraction method. Sickling of HbSS red blood cells was induced using sodium metabisulphite. Invitro antisickling activities of the crude extracts of the recipes were evaluated using phydroxybenzoic acid and normal saline as positive and negative control respectively. Readings were taken at different incubation time (0 – 180 min). The two recipes showed varied antisickling activities. At 90 min incubation period, Recipe 1 showed maximum percentage inhibition of 71.6 ± 1.21 while Recipe 2 showed 60.0±0.51 percentage inhibition. The inhibitory activity of Recipe 1 at 90 min incubation period was higher than that of the positive control (61.8 ± 2.28) and there was no significant difference (P < 0.5) in the inhibitory activity of Recipe 2 and the positive control. All plant constituents of the two recipes contained saponins and tannins (except Detarium microcarpum). The two indigenous recipes significantly demonstrated antisickling activity. The results of this study validate the use of the two recipes by indigenous people for the treatment of sickle cell disease. The isolation and identification of active phytochemicals responsible for the antisickling activity of Recipe 2 could lead to the discovery of novel drugs